A COMPARATIVE DOSE-RESPONSE STUDY BETWEEN INTRATHECAL NALBUPHINE (0.8 MG, 1.4 MG) WITH BUPIVACAINE HEAVY 0.5% 3.5 CC IN LOWER ABDOMINAL SURGERIES - SOMASUNDHAAR S, SAI; R, RATNA; ADAPA , SRINIVAS (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: To study the efficacy of various doses of nalbuphine as an additive in sub-arachnoid block for lower abdominal surgeries. Methods: This comparative study was conducted by the addition of two different doses of nalbuphine as an adjuvant: 0.8 mg nalbuphine hydrochloride to 0.5% bupivacaine (heavy) and 1.4 mg nalbuphine hydrochloride to 0.5% bupivacaine (heavy), the onset, maximum level, duration of sensory blockade, motor blockade, and hemodynamic parameters were studied. Results: It was discovered that group B (1.4 mg of nalbuphine added to 0.5% bupivacaine [H]) results in a later onset and greater degree of sensory and motor blockage. This group also considerably extended the time of analgesia, sensory and motor blockage, and both. The statistical examination of the mean blood pressure and mean pulse rate, together with the study of hemodynamic parameters, revealed that the p value was significant for the mean pulse rate and diastolic blood pressure but negligible for the systolic blood pressure. Conclusion: It can be concluded that intrathecal 0.5% bupivacaine (H)+nalbuphine (1.4 mg) when compared to intrathecal 0.5% bupivacaine (H)+nalbuphine (0.8 mg) in the patients undergoing lower abdominal surgeries.